2021
DOI: 10.1155/2021/9946015
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis Reveals Key Genes and Signalings Associated with the Prognosis of Prostate Cancer

Abstract: It is urgent to identify novel biomarkers for prostate cancer (PCa) prognosis and to understand the mechanisms regulating the tumorigenesis for PCa treatment. In this study, GSE17951 and TCGA were used to identify the differentially expressed genes (DEGs). Our study demonstrated that 1533 genes with increased expression and 2301 genes with decreased expression in PCa. Bioinformatics analysis data indicated that these up-regulated genes had an association with the modulation of mitotic nuclear division, sister … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…So, Shen H et al showed CCNB1 and CCNB2 genes are key factors in cell cycle pathways and the development of PC. These factors can suggest a novel prognosis and treatment biomarkers 53 . The molecules (POLQ, CDC20, MDM2, CCNB1, and CCNB2) have shown a slight increase in the LNCaP cell line treated with TH but studies have shown an increase in the expression of these molecules is associated with the progression of PC.…”
Section: Discussionmentioning
confidence: 99%
“…So, Shen H et al showed CCNB1 and CCNB2 genes are key factors in cell cycle pathways and the development of PC. These factors can suggest a novel prognosis and treatment biomarkers 53 . The molecules (POLQ, CDC20, MDM2, CCNB1, and CCNB2) have shown a slight increase in the LNCaP cell line treated with TH but studies have shown an increase in the expression of these molecules is associated with the progression of PC.…”
Section: Discussionmentioning
confidence: 99%